City of Words. A Multimodal Collaboration in ‘Writing Urban Places’ - Pauwels, Luc; Moloney, Anna Ryan (Writingplace, 2021)
This contribution is a collaborative effort of two scholars from different disciplinary and geographic backgrounds joined by an interest in producing and communicating urban narratives. Their partnership resulted in an experiment that combines aspects of different research and communication methods into a hybrid end-result: a collaborative multimodal essay. First, the methodological particularities of this collaborative effort will be discussed and situated within number of established and emerging visual methods: the blending of methods, the researcher roles, the distinct modes of expression and the different positions vis-a-vis the site under scrutiny (‘visitor’ versus ‘resident’; ‘outsider’ versus ‘insider’). This section will then be followed by the actual multimodal essay on the city of Limerick as a distinct form of scholarly communication balancing between art and science.